A Web-Based Authoring Tool for Scripting Distributed Pair Programming - Tsompanoudi, Despina; Satratzemi, Maya (2014 IEEE 14th International Conference on Advanced Learning Technologies, 2014)
SCEPPSys is a distributed pair programming system especially designed to support the application of pair programming in computer science courses. Compared to other implementations, SCEPPSys enables students to solve programming assignments guided by collaboration scripts. This approach exploits the benefits of collaborative learning in pair programming, and aims to maximize learning outcomes by structuring the problem-solving process. The system consists of a shared programming environment, which runs as a part of the Eclipse IDE, and a web-based administration environment. The main focus of this paper is to present an overview of the system and a detailed description of the features of the administration section, which contains an authoring tool for collaboration scripts and instructional support tools. The incorporation of various group formation strategies and the analysis of students' interactions make this software particularly useful for educators as well as researchers.